“Correlation is the Truth of all Existence,” or Interdisciplinarity as a Methodological Principle of Adequate Social Cognition - Serebryakov, Fanil Fagimovich (International Journal of Criminology and Sociology, 2022)
The article demonstrates that interdisciplinarity is not only a characteristic of the modern stage of scientific knowledge, as it is usually stated. Nevertheless, it is a methodological expression of the ambiguous nature of knowledge about any social subject, which makes us consider it as a requirement for adequate social knowledge. This nature of knowledge about a social subject stems from the fact that every existing thing (including a social one), always, “by nature” in relations with other things, discovers that it is itself (“the truth of its existence”), only through this relationship, only through another thing, only in interaction with it. We can call this the nature of a thing; the way it exists. Moreover, if all the definitions of a thing, all knowledge about a thing that arises specifically, as a result of its various relationships with other things, are essential for its understanding and cannot be ignored when defining a thing. Then an adequate knowledge of such a thing (social things) will always be only its knowledge as the dialectical unity of many definitions. This implies that the external expression of this fact is interdisciplinarity as a methodological principle of adequate knowledge. That is, adequate knowledge of a thing (which is always multifaceted) is possible only through the interaction of the potential of separate, historically developed systems of concepts that correspond to these faces and form separate social disciplines, i.e. only as interdisciplinary knowledge.